A Test of Spatial Contiguity for Virtual Human's Gestures in Multimedia Learning Environments. (September 2015) - Craig, Scotty D.; Twyford, Jessica; Irigoyen, Norma; Zipp, Sarah A.
Virtual humans are becoming an easily available and popular component of multimedia learning that are often used in online learning environments. There is still a need for systematic research into their effectiveness. The current study investigates the positioning of a virtual human's gestures when guiding the learner through a multimedia presentation. Using predictions based on the spatial contiguity principle of the Cognitive Theory of Multimedia Learning, learners were presented with a multimedia environment presented by a virtual human that did not gesture to guide the learning, gestured with item-specific gestures, or made general gestures close to the item area. The study randomly assigned 77 participants to one of the three conditions. The results indicated that having an agent perform gestures that are specifically targeting the elements discussed or in close vicinity can improve retention. These findings are taken as partial support for of the application of the spatial contiguity principle to virtual humans within multimedia environments.